Prevalence of arsenic-induced skin lesions and associated factors in Ethiopia: Community-based study - Solomon Demissie; Seblework Mekonen; Tadesse Awoke; Birhanu Teshome; Bezatu Mengistie (Toxicology Reports, 2023)
The study aimed to assess the prevalence of arsenic-induced skin lesions and associated factors among the population in the Adami Tulu Jido Kombolcha district, Ethiopia. A community-based cross-sectional study design was employed among 403 participants from June 02–20, 2022. A two-stage cluster sampling method was conducted to select study subjects. A pretested structured and semi-structured interview questionnaire and observation using a WHO flow chart were used for data collection. Data analysis was performed using SPSS version 24 statistical software for Windows. A multivariable binary logistic regression model was applied to examine the relationship between predictor variables and an outcome variable. The degrees of association between outcomes and predictor variables were assessed using ORs and 95% CIs, and P-values < 0.05 were considered significant. The prevalence of arsenic-induced skin lesions (arsenicosis) in the study area was 2.2% [95% CI: 1.0–3.7]. The most common arsenic-induced manifestation was keratosis (55.6%), followed by hyperpigmentation (33.3%) and hyperkeratosis (11.1%). Consumption of well water, smoking cigarettes, and chewing khat were significantly associated with arsenic-induced skin lesions. Therefore, the findings of this study should trigger further research on arsenic exposure and health risks.